Attitudes towards persons with disabilities among Occupational Therapy Students in UiTM Selangor/ Nur Suria Mohamad and Ahmad Kamal Mohd Natar - Mohamad, Nur Suria; Mohd Natar, Ahmad Kamal (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Background: Attitudes was a crucial factor and inner power that give character and purpose to what professionals do. Person with a disability was defined the person who has long-term physical, mental, sensory or intellectual impairments, which in interplay with diverse barriers that may prevent their full and efficient participation in society. The attitudes of health professional could be affect the person's beliefs about herself or himself as well as the process of rehabilitation. Aim: This study was conducted to compare attitudes towards person with disabilities among occupational therapy students within the demographic profile. Method: A cross-sectional study conducted involving 62 participants in first-year and final-year occupational therapy students in UiTM Selangor. All the participants need to answer an online questionnaire which consist of two part. Part 1 consists of demographics items, and Part 2 consists of Attitude toward Disabled Person-original form (ATPD-O) instrument was used to determine the attitudes towards person with disabilities. Result: From 62 participants, 54.8% of final-year students have higher attitudes towards person with disability (n=34) and 45.2% of first-year students have lower attitudes towards person with disability (n=28). An Independent-t test had determined that there are significant differences between the ATPD-O score and the demographic factors. Conclusion: There are significant different between the attitudes towards person with disabilities with level of education and gender while there are no significant difference between the attitudes towards person with disabilities with experience with disability, disabled relative and experience with clinical training.